2015
DOI: 10.1016/j.bbadis.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

NDRG1 attenuates epithelial–mesenchymal transition of nasopharyngeal cancer cells via blocking Smad2 signaling

Abstract: N-myc downstream-regulated gene 1 (NDRG1) has been implicated in tumorigenesis and metastasis in different cancers. However, its role in nasopharyngeal carcinoma remains unknown. We found that NDRG1 expression level was high in nasopharyngeal cancer 5–8F cells but low in 5–8F-LN cells with lymphatic metastasis potential. Knockdown of NDRG1 by shRNA promoted 5–8F cell proliferation, migration, and invasion in vitro and its tumorigenesis in vivo. Moreover, NDRG1 deficiency induced an epithelial-mesenchymal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
5
23
0
Order By: Relevance
“…As a group of intracellular proteins, SMADs are involved in transforming growth factor beta (TGFβ) signaling in cancer progression and metastasis (12). A previous study has suggested that SMAD2 signaling is involved in the inhibition of EMT in NPC cells (13). Moreover, miR-145 overexpression has been found to inhibit invasion and metastasis in NPC cells by targeting SMAD3 (14).…”
Section: Introductionmentioning
confidence: 99%
“…As a group of intracellular proteins, SMADs are involved in transforming growth factor beta (TGFβ) signaling in cancer progression and metastasis (12). A previous study has suggested that SMAD2 signaling is involved in the inhibition of EMT in NPC cells (13). Moreover, miR-145 overexpression has been found to inhibit invasion and metastasis in NPC cells by targeting SMAD3 (14).…”
Section: Introductionmentioning
confidence: 99%
“…The role of NDRG1 as a metastasis suppressor in CRC has been explored. It is reported that NDRG1 was involved in the metastasis of tumor by inhibiting EMT . The anti‐metastatic activity of NDRG1 in CRC could occur through the down‐regulation of nuclear β‐catenin .…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested that NDRG1 involved in mCRC though EMT via NF‐κB signaling pathway. NDRG1 has been demonstrated to inhibit EMT and restore the epithelial markers levels though TGF‐β, Smad2 signaling, or Wnt/β‐catenin pathways . Recent study suggested that NDRG1 played a significant role in regulating cancer cell migration by inhibiting Src activity, which involved in EMT and the development of metastasis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential role of NDRG1 in resistance of gastric cancer cells to MET pathway inhibition implicated by these data points is suggested by the role of NDRG1 in multidrug resistance in neuroblastoma cells (102). Moreover, its stabilization of the epithelial state in nasopharyngeal cancer cells (103) is consistent with the association between resistance to the MET inhibitor KRC-108 and transition to an epithelial phenotype (104). The Transcriptomine NDRG1 Regulation Report (https://goo.gl/ F76hnk) (accessed by clicking on the Transcriptomine query link in the FCI window of one of the NDRG1 data points) highlighted repression of Ndrg1 by the NR Rev-erbAa/Nr1d1 (data file S1, Query 17) (105,106).…”
Section: Drilling Down Places Data Points In Context and Enables Theimentioning
confidence: 92%